Bibliometric Mapping of Nurse-led Weaning ventilator in Chronic Disease Patients: Research Trends, Scientific Collaboration, and Conceptual Evolution in Critical Care Nursing (2000–2026 - Ade Rahmah Yulia; Yunie Armiyati; Aric Vranada; Chanif Chanif (Universitas Malahayati Lampung, 2026)
ABSTRACT Ventilator weaning is a critical stage in the management of patients receiving mechanical ventilation, contributing to the reduction of complications, length of hospital stay, healthcare costs, and mortality rates. The growing implementation of nurse-led ventilator weaning has increased the volume of scientific publications, highlighting the need for a comprehensive mapping of research developments in this field. This study aimed to analyze global research trends, scientific collaboration patterns, and thematic developments related to nurse-led ventilator weaning among patients with chronic diseases between 2000 and 2026. A bibliometric approach was employed using publications retrieved from the Dimensions database. The identification and selection process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. A total of 19,589 publications were initially identified, and after the screening process, 7,988 publications were included for analysis. Bibliometric analyses were conducted using VOSviewer version 1.6.20, including publication trend analysis, research field distribution, keyword co-occurrence analysis, network visualization, overlay visualization, and density visualization. The results demonstrated a dynamic development of publications related to nurse-led ventilator weaning throughout the study period. The dominant research fields were Biomedical and Clinical Sciences (7,722 publications), Health Sciences (5,466 publications), Clinical Sciences (2,324 publications), and Nursing (930 publications). Keyword co-occurrence analysis identified three major research clusters focusing on mechanical ventilation and the weaning process, patient safety and clinical outcomes, and evidence-based practice alongside clinical guideline development. Overlay visualization revealed a shift in research focus from the technical aspects of mechanical ventilation toward evidence-based practice implementation, patient safety, and quality improvement in critical care nursing. This study highlights the growing importance of nurse-led ventilator weaning as a multidisciplinary research area with substantial contributions to evidence-based critical care nursing practice. The findings provide valuable insights for future research, particularly regarding specific chronic diseases, digital health integration, and community-based ventilatory care. Keywords: Bibliometric Analysis, Weaning ventilator, Mechanical Ventilation, Critical Care Nursing, Nurse-Led Weaning.ABSTRAK Weaning ventilator merupakan tahapan penting dalam pengelolaan pasien yang menjalani ventilasi mekanik dan berperan dalam menurunkan komplikasi, lama rawat inap, biaya pelayanan kesehatan, serta mortalitas. Perkembangan pendekatan nurse-led ventilator weaning mendorong meningkatnya jumlah publikasi ilmiah sehingga diperlukan pemetaan penelitian secara komprehensif. Penelitian ini bertujuan menganalisis tren penelitian global, pola kolaborasi ilmiah, dan perkembangan tema penelitian mengenai nurse-led ventilator weaning pada pasien penyakit kronis selama periode 2000–2026. Penelitian ini menggunakan metode bibliometrik dengan sumber data dari database Dimensions. Proses identifikasi dan seleksi publikasi dilakukan menggunakan pendekatan PRISMA. Sebanyak 19.589 publikasi teridentifikasi dan setelah proses penyaringan diperoleh 7.988 publikasi yang dianalisis menggunakan perangkat lunak VOSviewer versi 1.6.20. Analisis meliputi tren publikasi, distribusi bidang penelitian, keyword co-occurrence, network visualization, overlay visualization, dan density visualization. Hasil penelitian menunjukkan bahwa publikasi mengenai nurse-led ventilator weaning mengalami perkembangan yang dinamis selama periode pengamatan. Bidang penelitian didominasi oleh Biomedical and Clinical Sciences (7.722 publikasi), Health Sciences(5.466 publikasi), Clinical Sciences (2.324 publikasi), dan Nursing (930 publikasi). Analisis kata kunci mengidentifikasi tiga klaster utama penelitian yang berfokus pada ventilasi mekanik dan proses weaning, keselamatan pasien serta luaran klinis, dan praktik berbasis bukti beserta pengembangan pedoman klinis. Overlay visualization menunjukkan pergeseran fokus penelitian dari aspek teknis ventilasi mekanik menuju implementasi evidence-based practice, keselamatan pasien, dan peningkatan mutu pelayanan keperawatan kritis. Penelitian ini menunjukkan bahwa nurse-led ventilator weaning berkembang sebagai area penelitian multidisiplin dengan kontribusi yang semakin besar terhadap pengembangan praktik keperawatan kritis berbasis bukti. Temuan ini dapat menjadi dasar untuk pengembangan penelitian lanjutan terkait penyakit kronis spesifik, integrasi teknologi digital, dan pelayanan ventilasi berbasis komunitas. Kata Kunci: Bibliometric Analysis, Weaning ventilator, Mechanical Ventilation, Critical Care Nursing, Nurse-Led Weaning.